Role of halalan thoyyiban consumption - Salleh, Hamzah Mohd.; Kartika, Betania (2020)
Muslims are aware that eating is not solely to satisfy hunger; rather it is a divine prescription that has its own inherent and distinct worth– Halalan Toyyiban consumption. It becomes clear that not consuming Halalan Toyyiban and consuming the unlawful (haram) instead may be a possible way of following the steps of Satan (Qur’an, 2:168), and will result in undesirable consequences.